Local Economic Institutional Capacity Development (Comparative Study in Value Perspective) - Akadun Akadun (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2022)
The performance of local economic institutions in a country is very strategic to improve the welfare of citizens. Therefore, research on strategies for developing local economic institutions to improve their performance is very significant. This study aims to compare several strategies for developing economic institutions in several countries. More specifically, this study compares the value systems that support local economic institutional performance. The effectiveness of local economic institutional capacity development is not only determined by the professionalism of managers, determination of the type of business, community involvement, and innovative management systems but is also influenced by the integration of the local economic institutional development program with development planning, visionary local leadership, and a supportive value system. Therefore, the makers and implementers of the local economic institutional capacity development program not only pay attention to the professionalism of managers, determining the type of business, community involvement, and innovative management systems but are also required to integrate the local economic institutional capacity development program with development planning, requiring visionary local leadership, adequate management default, and have a value system that supports performance.